The role of customer inspiration and relationship quality in engaging the online experience: insights from Kuwait and Portugal - Al-Reesh, Muhammad Saleh (2022)
The main research objective of the current thesis is to analyse the relationship between the online experience and customer engagement considering moderators and mediators and compare between Kuwait and Portugal. The thesis provides a systematic literature review on the online experience, customer inspiration, relationship quality, customer engagement, e-commerce, and national culture. Next, we conducted in-depth interviews with seven participants from Kuwait and Portugal, which allowed us to understand similarities and differences in online customer purchasing experience perceived by Kuwait and Portuguese customers and contributed to creating the conceptual model to be analysed in the quantitative approach. We used two Qualtrics panel samples for the qualitative research, one with 210 participants from Kuwait and another with 240 from Portugal. Major findings reveal that (i) customer empowerment strengthens the relationship between customer perceived value and online engagement, (ii) cooperation, e-commerce, and cultural perceptions are three relevant factors contributing to form three clusters of participants from Kuwait and Portugal, (iii) both online relationship quality and customer inspiration act as mediators in the relationship between the online experience and customer engagement, (iv) and finally there are differences between Kuwait and Portugal in engaging online, based on cultural differences. Managers can benefit from our research by offering an immersive online experience to their customers. Through stimulating online experiences, firms can inform customers about their products and services, educate their stakeholders about various subjects and, above all, manage a collaborative and participatory digital environment.